Impact of Probing the Reproductive Tract During Early Pregnancy on Fertility of Beef Cows - Pugliesi, G.; Scolari, S. C.; Mesquita, F. S.; Maturana Filho, M.; Araujo, E. R.; Cardoso, D.; Sales, J. N.; Martin, I. [UNESP]; Sa Filho, M.; Bertan, C. M. [UNESP]; Binelli, M. (Wiley-Blackwell, 2014)
This short communication reports the impact of endometrial biopsies, uterine flushings and follicular fluid aspiration procedures at day 6 post artificial insemination (AI) on pregnancy rates. In Experiment 1, cows were timed AI (TAI) and assigned to the following treatment groups: control (n = 37), uterine flushing (n = 35) and endometrial biopsy (n = 38). On day 30 post AI, pregnancy rates were 40.5%, 33% and 28.5%, respectively (p > 0.1). Pregnancy rate on day 60 was lower (p < 0.004) in flushed cows than in the controls. In Experiment 2, oestrus was detected and cows were assigned to flushing (n = 32) or biopsy (n = 33) treatments 6 days after AI, which resulted in pregnancy rates of 31% and 36%, respectively (p > 0.1). In Experiment 3, cows were, 6 days after TAI, randomly assigned to the following treatments: control (n = 84) or aspiration of the largest follicle (n = 73). Pregnancy rates on day 30 post AI were 63.5% for the control group and 53% for the aspirated group (p > 0.1). In conclusion, uterine flushing and endometrial biopsy negatively affect pregnancy rates, but neither procedure can be considered to be incompatible with pregnancy maintenance. Follicular aspiration during pregnancy does not interact with pregnancy success. The amount and quality of samples obtained are compatible with the use of cellular and molecular analysis of uterine variables from cows that failed or succeeded on maintaining pregnancy.